Age and Gender-Specific Reference Intervals for Uric Acid Level in Children Aged 5–14 Years in Southeast Zhejiang Province of China: Hyperuricemia in Children May Need Redefinition - Dai, Chengjun; Wang, Chaoban; Xia, Fangqin; Liu, Zishuo; Mo, Yiqi; Shan, Xiaoou; Zhou, Yonghai (Frontiers in Pediatrics, 2021)
Context: Hyperuricemia is defined when the plasma uric acid concentration is above 416μmol/L (7 mg/dl) in male adults, or 357μmol/L(6mg/dl) in female adults. However, there are no explicit criteria yet for children. Objective: It is necessary to set up reference intervals for the uric acid level in different age groups among children. Materials and methods: A total of 5439 individuals (3258 males, 2181 females) were included in the final statistical analysis. Reference values of all age groups were determined by statistical descriptions. Multiple linear regression analysis was applied to determine the relationship between uric acid level, BMI and age. Results: The level of uric acid increased with age. Gender differences in uric acid level occurred after the onset of puberty. Additionally, linear regression revealed a positive correlation between the uric acid level and BMI. Discussion and conclusion: The reference range of the uric acid level in children is inconsistent with the previous viewpoint. Body mass index plays an important role in uric acid metabolism.